Effects of Cognitive and Aerobic training on Working Memory and Executive Function in Aging, a Pseudo-Randomized Trial: Pilot Study - Clemence, Joubert; Hanna, Chainay (Journal of Aging Research And Healthcare, 2019)
Introduction Cognitive and physical (especially aerobic) training have been reported to enhance cognition in the elderly. The goal of this study was to compare the effectiveness of two types of training, namely combined cognitive-and-physical training and cognitive training alone, for cognition and in particular for executive function and working memory. Material and Method Healthy older adults (aged 65–86 years) were included in cognitive-and-physical - CAP (n=16) - or cognitive - COG (n=16) - training groups or in a passive control group – CONT (n=16). The training took place in 60-minute sessions conducted twice a week for 8 weeks. Cognitive functions were assessed before and immediately after the interventions and at a 1-month follow-up. Results In the short-term, the CAP and COG groups showed a transfer on updating, unlike the CONT group. In the long-term, although the gains achieved by both CAP and COG persisted, the benefit observed in the COG group was greater than that in the CAP group. Conclusion Our data suggest that there may be a complementarity between cognitive and physical training effects at the level of short-term transfer, given that physical training was able to boost cognitive training. Moreover, regarding transfer, physical training may help improve performance on untrained tasks. However, as far as the long-term persistence of the benefits of training is concerned, the results tend to indicate the superiority of cognitive training.
Keywords: Cognitive and physical training; cognitive enhancement; normal aging